Effect of gas temperature on CO2+ ion transport in CO2. (31st March 2020) - Diomede, P; Longo, S
Abstract: The effect of gas temperature on the transport of the CO2 + ion in its parent gas CO2 is studied. For this purpose, a Monte Carlo (MC) solution technique of the ion transport equation developed in the past by the authors, which was formally proven to provide the exact solution of the transport equation, is used. The study is performed first by benchmarking against experimental data and another MC code, using cross sections from literature and then changing the gas temperature. The solution is characterized through its moments such as reduced mobility, coefficients of its expansion in Legendre polynomials and three-dimensional ion velocity distribution function. It is shown that the gas temperature has a significant effect on all these quantities. This finding has important consequences for plasma modeling which are discussed.